Influence of ultrasound and microwave-assisted vacuum frying on quality parameters of fried product and the stability of frying oil. Issue 5 (26th March 2021) - Devi, Shoma; Zhang, Min; Mujumdar, Arun S.
Abstract: Vacuum frying (VF), which combines sonication, with microwave heating was used to evaluate the quality attributes of fried mushroom chips as well as the stability of the frying oil. Frying was performed at 90 °C, 0.015 MPa, 1000 W microwave power input at two ultrasound power levels. Mushroom ( Agaricus bisporus ) chips were fried using four frying conditions, namely: VF, microwave vacuum frying (MVF), 300 W ultrasound-assisted MVF (300UMVF), and 600 W ultrasound-assisted MVF (600UMVF). The fried samples were evaluated in terms of their moisture content, oil content, protein content, bioactive compounds (total phenolic compound, total flavonoid compound), and color characteristics. The 600UMVF sample required less processing time to reach at the same final moisture content. The oil content was also found to be lower in the high-power sonicated sample. The contents of protein, total phenolic compound, and total flavonoid compound in the fried mushroom chips (FMC) were preserved to a greater extent by the ultrasound treatment. All fried samples displayed natural color; the best result found for the 600UMVF sample. UMVF was found to delay oil deterioration by enhancing its oxidative stability. Microstructure observations revealed that the cell structure of the fried sample is preserved better by the ultrasound treatment. The findings of this work show that sonication-enhanced frying minimizes the loss of nutrients, bioactive compounds, and preserves the color of the original sample.